The Structure of the Threshold and The Epilogue in Kurdish Folk Tales - Saleh, Mohsen; Ibrahim, Aram (Humanities Journal of University of Zakho, 2021)
Since the beginnings of the circulation of folk tales, the narrator has tried in a way to show some of his touches on the tale. This means that the narrator, by narrating a short or long introduction in some cases, tried to set a threshold for the tale, which became an entrance to the content and events of the tale. He also tried to put an end to it as well, thus showing his role clearly in the narration and the arrangement of the events of the story, which in the advanced stages turned into a well-established habit that the narrator resorted to while telling his folk tales, which consequently led to the emergence of the structure of the threshold and the epilogue appeared in the story.In this research, the following questions are asked. What are those styles that are used in the threshold and epilogue of the Kurdish folk tales? Is there a approach between those styles in the Kurdistan? Through this, an attempt was made to study (38) books on the folklore story and tale, in order to indicate the style of each structure separately according to the different area and places in the Great Kurdistan. This study is entitled: (The structure of the threshold and the epilogue in Kurdish folk tales).